پاڵنەرەکانی خوێندن لە زانکۆ تایبەتەکان توێژینه‌وه‌یه‌كی مه‌یدانیه‌ له‌ شاری سلێمانی - كریم, لقمان صالح; حسن, هێمن محمود (Sulaimani Journal for Humanities, 2023)
Summary: The main objective of this research is to identify the drives that encourage the students to enroll in a private university to complete their study. Through applying the descriptive approach, the researcher sought to highlight and showcase the impact of those different drivers that were highlighted in this study, namely the (economic motivations, psychological motivations, social motivations and scientific or academic drives) in addition to displaying the differences between those drivers according to age, sex and place of residence. Among the most important statistical tools used in this research are the arithmetic mean, standard deviation, independent t-sample. One of the results the researcher concluded with is that there is a significant role for each of the economic and academic drivers, in particular, for students to choose a private university to complete their undergraduate studies, without any change in these two drivers by changing the sex of the students.